Teaching 'proper' drinking? : pubs and clubs in Indigenous Australia - Brady, Maggie (Research monograph (Australian National University. Centre for Aboriginal Economic Policy Research) ;, 2017)
In Teaching 'Proper' Drinking?, the author brings together three fields of scholarship: socio-historical studies of alcohol, Australian Indigenous policy history and social enterprise studies. The case studies in the book offer the first detailed surveys of efforts to teach responsible drinking practices to Aboriginal people by installing canteens in remote communities, and of the purchase of public hotels by Indigenous groups in attempts both to control sales of alcohol and to create social enterprises by redistributing profits for the community good. Ethnographies of the hotels are examined through the analytical lens of the Swedish 'Gothenburg' system of municipal hotel ownership. The research reveals that the community governance of such social enterprises is not purely a matter of good administration or compliance with the relevant liquor legislation. Their administration is imbued with the additional challenges posed by political contestation, both within and beyond the communities concerned.